Wanted: A vocabulary for talking about involuntary behaviors associated with Lesch‐Nyhan disease. Issue 1 (23rd March 2021) - Robey, Kenneth L.; Balboni, Daniel C.
Abstract: Lesch‐Nyhan disease (LND) is a rare genetic disorder with an unusual behavioral phenotype that includes severe and involuntary self‐injury requiring the near constant use of protective devices and, for some individuals, dental extraction. Often, the person with LND also engages in emotional self‐injury in the form of both self‐sabotage and behaviors directed toward others that will have a negative social consequence. When these self‐destructive behaviors present themselves, it is sometimes challenging for caregivers, professionals, or other observers to fully recognize their lack of volition. It is an even greater challenge to accurately and convincingly convey their involuntary nature to medical students, colleagues, school staff, or even family members who might be unfamiliar with the disorder. It is difficult to find words to clearly and adequately convey the essence of behaviors like those that we find in LND without, in some way, implying intent.